Cardiac resynchronisation therapy in patients with chronic heart failure. Issue 13 (16th April 2015) - Lalani, Gautam G; Birgersdotter-Green, Ulrika
Abstract : Cardiac resynchronisation therapy (CRT) is common treatment for congestive heart failure (HF) with decreased LV function and wide QRS complex. Its foundations are set in the understanding of the pathophysiology of ventricular dyssynchrony. Over the last several decades, CRT has evolved through changes in implantation techniques, device and lead design, imaging modalities and our growing clinical experience. This review article will discuss the vast clinical experience that has led to current guidelines recommendations for CRT in patients with mild-to-severe HF. In addition, the article will also discuss recent evidence of benefits of CRT in patients beyond the guidelines. The article will also address the issue of non-responders, optimisation of CRT, postimplant evaluation and remote monitoring.